Retention of corneodesmosomes and increased expression of protease inhibitors in dandruff. (1st October 2014) - Singh, B.; Haftek, M.; Harding, C.R.
Summary: Background: Dandruff is a common, relapsing and uncomfortable scalp condition affecting a large proportion of the global population. The appearance of flakes on the scalp and in the hair line, and associated itch are thought to be consequences of a damaged skin barrier, altered corneocyte cohesion and abnormal desquamation in dandruff. The balance between skin proteases and protease inhibitors is essential for driving the key events, including corneodesmosome degradation, in the desquamation process and to maintain stratum corneum (SC) barrier integrity. Objectives: To investigate the distribution of corneodesmosomes, the key component of the SC cohesivity and barrier function, and the protease inhibitors lympho‐epithelial Kazal‐type‐related inhibitor (LEKTI‐1) and squamous cell carcinoma antigen (SCCA1) in the scalp of dandruff‐affected participants. Methods: The methods utilized were immunohistochemistry, scanning immunoelectron microscopy, phase‐contrast microscopy, Western blotting and serine protease activity assay on tape‐stripped SC or scalp skin biopsies. Results: In SC samples from healthy subjects, corneodesmosomes were peripherally located in the corneocytes. In samples of dandruff lesions, corneodesmosomes were located both peripherally and on the entire surface area of the corneocytes. LEKTI‐1 and SCCA1 protein levels and parakeratosis were found to be highly elevated in the lesional samples. Conclusions: The persistence of nonperipheral corneodesmosomes is a characteristic feature of the perturbed desquamation seen in dandruff. The increased expression levels of LEKTI‐1 and SCCA1 are consistent with the view that the dandruff condition is characterized by an imbalance in protease–protease inhibitor interaction in the SC.